Fluorescent CXCR4 targeting peptide as alternative for antibody staining in Ewing sarcoma - Sand, Laurens G. L. (BMC Cancer, 2017)
BACKGROUND: Ewing sarcoma is an aggressive, highly metastatic primary bone and soft tissue tumor most frequently occurring in the bone of young adolescents. Patients, especially those diagnosed with a metastatic disease, have a poor overall survival. Chemokine receptor CXCR4 has a key pro-tumorigenic role in the tumor microenvironment of Ewing sarcoma and has been suggested to be involved in the increased metastatic propensity. Earlier studies on CXCR4 protein expression in Ewing sarcoma yielded contradictory results when compared to CXCR4 RNA expression studies. Previously, we demonstrated that CXCR4 expression could be detected in vivo using the fluorescently tagged CXCR4-specific peptide MSAP-Ac-TZ14011. Therefore, we studied the membranous CXCR4 expression in Ewing sarcoma cell lines using MSAP-Ac-TZ14011. METHODS: The CXCR4 membrane expression levels were studied in EWS cell lines by flow cytometry using the hybrid peptide MSAP-Ac-TZ14011 and were correlated to CXCR4 RNA expression levels. The measurements were compared to levels detected using the CXCR4 antibody ab2074 under various cell preparation conditions. In addition, the staining patterns were analyzed by confocal fluorescence microscopy over time. RESULTS: The hybrid peptide MSAP-Ac-TZ14011 levels showed a strong and better correlation of CXCR4 membrane expression with the CXCR4 RNA expression levels than observed with the anti-CXCR4 antibody ab2074. With the hybrid peptide MSAP-Ac-TZ14011 using live cell confocal microscopy CXCR4 membrane staining and internalization was detected and the signal intensity correlated well with CXCR4 mRNA expression levels. CONCLUSIONS: The fluorescently labeled CXCR4 targeting peptide-based method provides a reliable alternative to antibody staining to study the CXCR4 membrane expression in live cells using either flow cytometry or live cell fluorescence microscopy. The fluorescently tagged CXCR4 targeting peptide could enable in vivo detection of CXCR4 expression in Ewing sarcoma which may help to stratify cases for anti-CXCR4 therapy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-017-3352-z) contains supplementary material, which is available to authorized users.